Unconjugated bilirubin inhibits C1 esterase activity - Arriaga, Sandra Mónica María (2009)
Objective: To evaluate if unconjugated bilirubin (UB) inhibits C1 esterase activity. Design and methods: Esterase activity was evaluated by C1-mediated hydrolysis of N-acetyl-l-tyrosine ethyl ester, and binding of UB to C1r and C1s was assessed by dot-blot analysis. Results: UB inhibited C1 enzymatic activity. C1r, C1s and human serum albumin bound [14C]-UB to a similar extent. Conclusions: UB inhibits C1 esterase activity, apparently due to a direct pigment-protein interaction. This could explain the inhibitory action of UB on complement activation. © 2009 Elsevier Inc. All rights reserved.